Effect of tetracycline on experimental Venezuelan equine encephalitis - Negrette, Américo; Hernández, Hugo (Investigación Clínica, 2013)
The effect of tetracycline on experimental Venezuelan equine encephalitis was studied using three groups of embrionated chick eggs: one group was innoculated with viruses, a second group was innoculated with viruses and two hours later injected with tetracycline and a third group which received the tetracycline injection prior the innoculation with the viruses. It was observed that the group which did not receive tetracyc1ine showed 98.8% mortality, while in the groups injected with the antibiotic, the mortalitywas only 71.5%. No differences were observed between the prophylactic and therapeutic administration of the antibiotic.